AIR FLOW VISUALIZATION AROUND THE FLIGHT FLIGHT WINGS - Yosaphat Sumardi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2003)
This research is performed with objectives: (I) to show the patterns of velocity field contour of airflow around the wings of subsonic plane, (2) to show factors that influence these patterns, and (3) to explain their application in flight engineering. The patterns of velocity field contour of airflow are visualized by using numerical method in Femlab software. Varying the velocity of airflow, the angle of attack, and the cross section form of wings shows the visualization of these patterns. The results of research show that the patterns of velocity field contour of airflow around the wings of subsonic plane may be circulation form. Factors that influence these patterns of contour are the velocity of airflow, the attack angle of wings, and the cross section form of wings. These three factors determine lift coefficient and dragcoefficient. In commercial flight it is used airfoil wings that areequipped by rear flaps on the trail edge of wings. These rear flaps canbe lowered of raised to adjust the cross section of airfoil. The slotsetting in the leading edge of wings can reduce the drag coefficient.Accordingly.fuel efficiency andflight safety can be controlled.